Carbodiimide Inactivation of MMPs and Effect on Dentin Bonding. (March 2014) - Mazzoni, A.; Apolonio, F.M.; Saboia, V.P.A.; Santi, S.; Angeloni, V.; Checchi, V.; Curci, R.; Di Lenarda, R.; Tay, F.R.; Pashley, D.H.; Breschi, L.
The use of protein cross-linking agents during bonding procedures has been recently proposed to improve bond durability. This study aimed to use zymography and in situ zymography techniques to evaluate the ability of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) cross-linker to inhibit matrix metalloproteinase (MMP) activity. The hypotheses tested were that: (1) bonding procedures increase dentin gelatinolytic activity and (2) EDC pre-treatment prevents this enzymatic activity. The zymographic assay was performed on protein extracts obtained from dentin powder treated with Optibond FL or Scotchbond 1XT with or without 0.3M EDC pre-treatment. For in situ zymography, adhesive/dentin interfaces were created with the same adhesives applied to acid-etched dentin slabs pre-treated or not with EDC conditioner. Zymograms revealed increased expression of dentin endogenous MMP-2 and -9 after adhesive application, while the use of EDC as a primer inactivated dentin gelatinases. Results of in situ zymograpy showed that hybrid layers of tested adhesives exhibited intense collagenolytic activity, while almost no fluorescence signal was detected when specimens were pre-treated with EDC. The correlative analysis used in this study demonstrated that EDC could contribute to inactivate endogenous dentin MMPs within the hybrid layer created by etch-and-rinse adhesives.